A Rare Presentation of Coronavirus Disease 2019 (COVID-19) Induced Viral Myositis With Subsequent Rhabdomyolysis - Zhang, Qian (Cureus, 2020)
A 38-year-old gentleman with no significant past medical history but had recent COVID-19 exposure presented to the hospital with the chief complaints of fever, shortness of breath, and generalized myalgia. He was unfortunately found to be severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive. Laboratory findings showed creatine kinase (CK) >42,670 U/L along with elevated inflammatory markers and unremarkable creatinine, cardiac troponin level. The cause of his rhabdomyolysis was discovered to be due to COVID-19 as he had no evidence of other viral infections, strenuous exercise, seizure, or other nontraumatic exertional etiologies. He received aggressive fluid resuscitation while we trended his CK levels along with other inflammatory markers throughout his hospitalization course. His diffuse myalgia improved with treatments, and he was found to maintain stable hemodynamics and was subsequently discharged home.